Penerapan Konsep Maslahah dalam Asuransi Syariah - Navissya Dzuchroidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Sharia insurance is a mutual protection and assistance effort among several individuals/parties through investments in assets or tabarru'. Which provides a return pattern to address specific risks through a Sharia-compliant contract (aqad). Sharia insurance businesses have the benefit of protecting life, mind, property, and descendants. The implementation of maslahah in Sharia insurance is realized through transactions that begin with contributions in the form of tabarru'. In the determination of Islamic law, maslahah can be considered if it does not conflict with the principles of Islamic law. This study aims to analyze Sharia insurance from the perspective of the concept of maslahah. This study uses a qualitative approach with a literature review method to understand the philosophy of maslahah and its application in Sharia insurance. The results show that the principle of maslahah plays a significant role in the development of Sharia insurance.